Combined Effect of Walking and Forest Environment on Salivary Cortisol Concentration - Kobayashi, Hiromitsu; Song, Chorong; Ikei, Harumi; Park, Bum-Jin; Kagawa, Takahide; Miyazaki, Yoshifumi (Frontiers in Public Health, 2019)
We investigated the effects of walking in a forest environment on salivary cortisol concentrations. Seventy-four young male participants walked for 15 minutes in forested and urban environments, and saliva was collected before and after walking. Our previous study reported salivary cortisol concentrations after walking only. This study was aimed at clarifying the combined effects of walking and environment by comparing post-walking data with pre-walking data. Walking in a forest environment decreased mean cortisol concentration from 9.70 to 8.37 nmol/L, whereas walking in an urban environment barely changed mean cortisol concentration, from 10.28 to 10.01 nmol/L. Two-way repeated analysis of variance revealed a significant interaction effect between the environment and walking (p < 0.001) in addition to the main effects of each (p < 0.001 and p = 0.001, for walking and environment, respectively). For further analysis, the proportion of participants who exhibited decreased cortisol after forest-walking was compared with the previously reported proportion of participants who exhibited decreased cortisol after viewing forest landscapes. Although the proportion of positive responders was slightly higher after walking (69%) than it was after viewing (60%), this difference was not statistically significant (p = 0.093). The present study revealed a significant combined effect of walking and the environment on cortisol concentrations.